2005
DOI: 10.1210/en.2004-1532
|View full text |Cite
|
Sign up to set email alerts
|

Central Relaxin-3 Administration Causes Hyperphagia in Male Wistar Rats

Abstract: Relaxin-3 (INSL-7) is a recently discovered member of the insulin superfamily. Relaxin-3 mRNA is expressed in the nucleus incertus of the brainstem, which has projections to the hypothalamus. Relaxin-3 binds with high affinity to the LGR7 receptor and to the previously orphan G protein-coupled receptor GPCR135. GPCR135 mRNA is expressed predominantly in the central nervous system, particularly in the paraventricular nucleus (PVN). The presence of relaxin-3 and these receptors in the PVN led us to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
236
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(250 citation statements)
references
References 26 publications
(25 reference statements)
13
236
0
Order By: Relevance
“…Relaxin-3 is predominantly expressed in gamma-aminobutyric acid (GABA) neurons in the hindbrain nucleus incertus, which projects widely to forebrain areas, including the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus, and lateral hypothalamus, which also express high levels of RXFP3 (11,15,(17)(18)(19)(20)(21)(22). This pattern of innervation, along with findings that relaxin-3 can modulate (i) food intake (23)(24)(25), (ii) responses to stress (20,26,27), (iii) arousal (28,29), and (iv) interactions with the corticotropin-releasing factor (CRF) systems (20,26), led us to hypothesize that relaxin-3 may modulate aspects of behavior related to substance use and abuse. Such a role would parallel that of other neuropeptides, such as orexin/hypocretin (30,31), galanin (32), and melanin-concentrating hormone (33).…”
Section: Addiction | Dependencementioning
confidence: 80%
“…Relaxin-3 is predominantly expressed in gamma-aminobutyric acid (GABA) neurons in the hindbrain nucleus incertus, which projects widely to forebrain areas, including the amygdala, bed nucleus of the stria terminalis (BNST), hippocampus, and lateral hypothalamus, which also express high levels of RXFP3 (11,15,(17)(18)(19)(20)(21)(22). This pattern of innervation, along with findings that relaxin-3 can modulate (i) food intake (23)(24)(25), (ii) responses to stress (20,26,27), (iii) arousal (28,29), and (iv) interactions with the corticotropin-releasing factor (CRF) systems (20,26), led us to hypothesize that relaxin-3 may modulate aspects of behavior related to substance use and abuse. Such a role would parallel that of other neuropeptides, such as orexin/hypocretin (30,31), galanin (32), and melanin-concentrating hormone (33).…”
Section: Addiction | Dependencementioning
confidence: 80%
“…We have recently shown for the first time, that acute intracerebroventricular and iPVN administration of low dose H3 stimulates feeding in satiated male Wistar rats in the early light phase [12]. The lowest dose of H3 to elicit a significant orexigenic response when administered iPVN was seen in the picomolar range at 18 pmol, similar to other orexigenic peptides such as ghrelin and NPY.…”
Section: Introductionmentioning
confidence: 78%
“…We have recently demonstrated that relaxin-3 may play a role in the regulation of food intake [12]. The aim of the current study was to investigate the maximum orexigenic response elicited by H3.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Relaxin-3 and its receptor GPCR135 are both predominantly expressed in the brain (11,14), in particular in regions dealing with sensory signals (15,16). This finding, together with recent in vivo studies that revealed that relaxin-3 is involved in stress responses (17) and in regulation of feeding (18), suggest a physiological role in neuroendocrine and sensory processing. An interesting feature of relaxin-3 is its ability to activate both GPCR142 (19) and LGR7 (20) in addition to its own receptor, GPCR135 (11).…”
mentioning
confidence: 75%